Comparison of deep eutectic solvents (DES) on pretreatment of oil palm empty fruit bunch (OPEFB): Cellulose digestibility, structural and morphology changes. (June 2019) - Thi, Shiki; Lee, Kiat Moon
Graphical abstract: Highlights: DES pretreatment is effective in pretreating OPEFB. The pretreatment is affected by different DES acidity and alkalinity. Acidic ChCl-LA (1:2) has the best pretreatment performance with glucose yield of 20.7%. High glucose yield is attributed by severe structural disruption as analysed in SEM and FTIR. Abstract: In this work, a novel solvent, deep eutectic solvent (DES) was applied to examine its effectiveness in pretreating OPEFB. Three types of DESs, i.e. choline chloride-lactic acid (ChCl-LA), choline chloride-urea (ChCl-U) and choline chloride-glycerol (ChCl-G) were investigated. The pretreatment performance was based on cellulose digestibility, structural and morphology changes. At molar ratio of 1:2, ChCl-LA attained the highest reducing sugars yield of 20.7%, followed by ChCl-G (20.0%) and ChCl-U (16.9%). FT-IR and SEM results further confirmed the outstanding ability of ChCl-LA due of its ability in cellulose, hemicellulose and lignin disruption, exposing its cellulose fraction to enzymatic hydrolysis. ChCl-LA is also more favorable compare to acid and alkaline solvents as it could prevent sugars loss, use of expensive corrosion resistant equipment and ease products separation.